Outcome of Monochorionic Twins Conceived by Assisted Reproduction - Simões, T (2017)
OBJECTIVE: To evaluate monochorionic twins conceived by assisted reproductive technology (ART). DESIGN: We compared perinatal outcomes of monochorionic twins conceived by ART with their dichorionic counterparts and with spontaneous monochorionic twins. SETTING: Referral center. PATIENT(S): Mothers to monochorionic and dichorionic twins conceived by ART and spontaneous monochorionic twins. INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): Maternal characteristics, pregnancy complications, and perinatal outcomes. RESULT(S): Monochorionic twin pregnancies (n = 25) comprise 7.2% of all ART twins and 4.9% of all monochorionic twins in this data set. Monochorionic pairs have a significantly worse outcome compared with dichorionic sets in terms of lower gestational age and birth weight. ART appears to increase the already high risk of monochorionicity compared with spontaneous conception: odds ratio (OR), 2.9 (1.1-7.3) for preterm birth at <32 weeks and OR, 5.9 (2.5-1.49) for birth weight <1,500 g. CONCLUSION(S): Monochorionic twins after ART are at increased risk of adverse perinatal outcomes compared with spontaneous monochorionic twins and with dichorionic twins conceived by ART.